The effect of temperature in stable on the number of dairy cows lying in cubicles during the resting period of summer day - Navrátil, Stanislav; Falta, Daniel; Matěj, Benešovský; Chládek, Gustav (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2017)
The effects of stable temperature was investigated on the number of cows lying in cubicles during the resting period of the day. The experiment took place on the University Enterprise (49.011598N, 16.602572E) in Žabčice during August 2017. The 143 cows of Holstein cattle undertook the experiment in total. The number of cows lying, relative humidity and ambient temperature were recorded. The temperature was expressed by the environmental cooling rate that was calculated. The temperature-humidity index (THI) was calculated and correlation was computed with the number of cows that were lying in the cubicles. A moderate positive correlation was found between the number of lying cows and environmental cooling rate (r=0.50). The relationship between THI and the number of cows that were lying in the cubicles was negative (-0.25). The temperature showed a stronger negative correlation (r = -0.598) to number of cows lying in cubicles than THI. These results can be used for breeders to optimize their breeding environment.